One Belt One Road as Global Inclusive Growth Strategy of PRC - Wang, Yongshun; Ван, Юншунь (Ternopil : WUNU, 2025)
This dissertation examines the strategic role of One Belt One Road Initiative as a pivotal element of China’s international cooperation framework aimed at promoting inclusive growth. Situating the initiative within the evolving contexts of globalization, regional integration, and shifting geopolitical dynamics, the study explores the theoretical foundations, implementation mechanisms, and long-term strategic impacts of the BRI.
Один пояс один шлях як глобальна стратегія інклюзивного зростання КНР
Keywords: Belt and Road Initiative; international economic relations; global security; globalization; integration; international cooperation; export; import; China; international trade; investment; sustainable development; global economy; digitalization; green finance.